2014
DOI: 10.1186/1471-2407-14-171
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer symptom awareness and anticipated delayed presentation in a population sample

Abstract: BackgroundWhile ovarian cancer is recognised as having identifiable early symptoms, understanding of the key determinants of symptom awareness and early presentation is limited. A population-based survey of ovarian cancer awareness and anticipated delayed presentation with symptoms was conducted as part of the International Cancer Benchmarking Partnership (ICBP).MethodsWomen aged over 50 years were recruited using random probability sampling (n = 1043). Computer-assisted telephone interviews were used to admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
73
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 42 publications
17
73
3
1
Order By: Relevance
“…Majority of the women in our study had very poor knowledge of the symptoms and risk factors of ovarian cancer, even though their level of awareness of the disease was high. This is similar to the findings in several studies [2,6,14,20,25], which have consistently shown poor knowledge of the disease among women. In America, only 15% of the women reported they were either familiar or very familiar with the symptoms of ovarian cancer [20].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Majority of the women in our study had very poor knowledge of the symptoms and risk factors of ovarian cancer, even though their level of awareness of the disease was high. This is similar to the findings in several studies [2,6,14,20,25], which have consistently shown poor knowledge of the disease among women. In America, only 15% of the women reported they were either familiar or very familiar with the symptoms of ovarian cancer [20].…”
Section: Discussionsupporting
confidence: 92%
“…It is not surprising that women with tertiary level of education had significantly better knowledge as compared with their counterparts. This is similar to the findings in the United States and United Kingdom, where women with higher levels of education were more knowledgeable of the symptoms and risk factors of ovarian cancer [14,20]. Education is a known determinant of quality of life and health [27]; and educated women are probably more empowered to have a better understanding of health-related issues.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Despite rich and diverse research efforts, early detection and diagnosis of epithelial ovarian cancer (EOC) remains a significant challenge [3,4]. In the United States, approximately 22,000 women are diagnosed with EOC each year.…”
Section: Introductionmentioning
confidence: 99%
“…This is the possible reason for the delayed seeking of medical attention. The early symptoms include abdominal distension (bloating, increased abdominal size), pelvic and/or abdominal pain, problems with eating (loss of appetite, feeling full quickly), and frequent urination [5]. Based on the study done by Brain, et al [5], the most well-identified symptoms of ovarian cancer were post-menopausal bleeding (87.4%), and persistent pelvic (79.0%) and abdominal (85.0%) pain.…”
mentioning
confidence: 99%